2009
DOI: 10.1007/978-3-642-03655-2_33
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Goal-Directed Movements: Beyond Fitts’ Law

Abstract: Abstract. Various methods and measures have been developed to assess the quality of input devices and interaction techniques. One approach to investigating the performance of input devices and interaction techniques is to focus on the quality of the produced movements. The current paper proposes a new method of analyzing goal-directed movements by dividing them into meaningful phases. In addition to the proposed analysis method a selection of measures is suggested to assess different aspects of rapidly aimed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…This was confirmed in a study investigating 2D goal-directed movements carried out with a mouse and a stylus with a tablet. 10 This study demonstrated that the five phases' duration and other measures applied to the ballistic and correction phases can indeed provide more information about the movement strategies people use when interacting through different input devices.…”
Section: Movement Parsingmentioning
confidence: 79%
See 1 more Smart Citation
“…This was confirmed in a study investigating 2D goal-directed movements carried out with a mouse and a stylus with a tablet. 10 This study demonstrated that the five phases' duration and other measures applied to the ballistic and correction phases can indeed provide more information about the movement strategies people use when interacting through different input devices.…”
Section: Movement Parsingmentioning
confidence: 79%
“…From this assumption and our study of many velocity profiles, we concluded that we could robustly distinguish five phases: latency, initiation, ballistic, correction, and verification (see Figure 1). 10 The latency phase starts when the task is set and ends when the actual movement starts. The initiation phase consists of small movements made before the ballistic phase.…”
Section: Movement Phasesmentioning
confidence: 99%
“…This contention is supported by [1], who described Fitts' Law as a gross measure (one outcome per test), not providing detail on the movement during a trial. For this reason, other research [9] had identified a need to develop additional measures that account for variations in goal-directed movements as a function of time.…”
Section: A Overall Movement Characteristicsmentioning
confidence: 97%
“…While there has been extensive research describing target acquisition movements, the tasks selected for these studies have primarily been repeated trials of artificial point-to-point target acquisition tasks [9,19]. Alternatively, existing psychomotor tasks, including the Purdue Pegboard Test [20], the Minnesota Manual Dexterity Test [21] and the Block Design (BD) test [22] feature a target acquisition component, but also have been validated for use in applied settings such as physical therapy, occupational therapy, vocational evaluation and employment screening [21].…”
Section: B Submovement Structurementioning
confidence: 99%
See 1 more Smart Citation